Pre-Procedural C-Reactive Protein Level Predicts In-Hospital Outcome in Percutaneous Coronary Intervention (Cardiovascular Journal, 2012)
Background:To accurately stratify patients undergoing PCI, according to their risk of future adverse events, a quest for risk predictors is ongoing worldwide. But only a few powerful and independent predictors of early and late major adverse cardiovascular events have been found. These include traditional risk factors, such as acute coronary instability, diabetes mellitus, reference vessel diameter, and lesion and/or stent length. This study was undertaken to find out the relationship between pre-procedural CRP level with in-hospital (both procedural and before discharge) complications. Materials & methods: This prospective study was carried out in National Institute of Cardiovascular Diseases (NICVD), Dhaka during the period of June,2006 to May,2007. After fulfilling the exclusion criteria, 100 consecutive patients were selected as sample those underwent percutaneous coronary intervention. C-Reactive protein (CRP) was measured in all patients before the procedure. Those having pre-procedural CRP level